1872 N.J. Laws 17 - (:unkn) unknown (My University, 1872)
Ch. 85, 3: It shall not be lawful for any person or persons passing, riding or driving over any toll bridge, as aforesaid, to carry any lighted cigar or pipe, or to carry fire in any form, or to light any match, or cigar, or pipe, or to fire off any gun, or other fire arms, or to explode any fireworks of any description, on said bridge, or within its enclosures[.]
Keywords: DISCHARGE